Dancing across borders the American fascination with exotic dance forms - Shay, Anthony 1936- (McFarland, 2008)
"This study describes and analyzes the phenomenal popularity of exotic dance forms among mainstream Americans. Throughout the 20th century, millions of Americans have begun learning and performing various Balkan dances, the tango, and other Latin American dances, along with the classical dances of India, Japan, and Indonesia"--Provided by publisher.
"This study describes and analyzes the phenomenal popularity of exotic dance forms among mainstream Americans. Throughout the 20th century, millions of Americans have begun learning and performing various Balkan dances, the tango, and other Latin American dances, along with the classical dances of India, Japan, and Indonesia"--Provided by publisher.
Includes bibliographical references and index
Keywords: Geschichte; Gesellschaft; Dance -- Social aspects -- United States; Dance -- United States -- History; Dance -- Anthropological aspects; Sex in dance; Tanz; USA